2020
DOI: 10.3390/ijerph17113911
|View full text |Cite
|
Sign up to set email alerts
|

A Practical Approach to Using Integrated Knowledge Translation to Inform a Community-Based Exercise Study

Abstract: Background: Our aim was to understand cancer survivor needs prior to, and following the Alberta Cancer Exercise (ACE) pilot randomized trial as a means to inform implementation of a province-wide cancer-specific, community-based exercise program. Methods: Questionnaires and semi-structured stakeholder engagement sessions were conducted with cancer survivors to explore preferences, barriers and facilitators/benefits at two timepoints: (1) pre-ACE: prior to initiation of the ACE pilot trial (n = 13 survivors and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
(40 reference statements)
0
9
0
Order By: Relevance
“…The included studies were mapped onto the KTA cycle [ 29 ] based on the reported research purpose and objectives, as follows: identify problem ( n = 30) [ 37 – 67 ]; adapt knowledge to local context ( n = 34) [ 37 40 , 43 , 44 , 46 , 49 , 52 , 55 , 56 , 61 , 62 , 64 , 65 , 67 – 86 ]; assess barriers/facilitators to knowledge use ( n = 14) [ 39 , 40 , 52 , 56 , 63 , 68 , 72 , 74 , 81 , 83 , 87 – 90 ]; select, tailor, implement interventions ( n = 11) [ 56 , 63 , 68 , 80 , 81 , 83 , 88 – 92 ]; monitor knowledge use ( n = 25) [ 55 , 63 – 65 , 69 , 73 , 80 , 83 , 89 , 91 107 ]; evaluate outcomes ( n = 22) [ 48 , 50 , 51 , 62 , 64 , 68 , 71 , 79 , 83 , 91 , 93 , 95 , 100 – 110 ]; sustain knowledge use ( n = 1) [ 79 ...…”
Section: Resultsmentioning
confidence: 99%
“…The included studies were mapped onto the KTA cycle [ 29 ] based on the reported research purpose and objectives, as follows: identify problem ( n = 30) [ 37 – 67 ]; adapt knowledge to local context ( n = 34) [ 37 40 , 43 , 44 , 46 , 49 , 52 , 55 , 56 , 61 , 62 , 64 , 65 , 67 – 86 ]; assess barriers/facilitators to knowledge use ( n = 14) [ 39 , 40 , 52 , 56 , 63 , 68 , 72 , 74 , 81 , 83 , 87 – 90 ]; select, tailor, implement interventions ( n = 11) [ 56 , 63 , 68 , 80 , 81 , 83 , 88 – 92 ]; monitor knowledge use ( n = 25) [ 55 , 63 – 65 , 69 , 73 , 80 , 83 , 89 , 91 107 ]; evaluate outcomes ( n = 22) [ 48 , 50 , 51 , 62 , 64 , 68 , 71 , 79 , 83 , 91 , 93 , 95 , 100 – 110 ]; sustain knowledge use ( n = 1) [ 79 ...…”
Section: Resultsmentioning
confidence: 99%
“…Despite the growing evidence for the benefit of exercise, overall physical activity levels of individuals with cancer both during and following cancer treatment remain low [ 49 ]. Therefore, improving uptake among those less inclined to exercise will require the integration of strategies such as oncologist recommendation [ 18 ], healthcare provider counseling on exercise options [ 18 , 26 , 50 ], and a tailored multicomponent approach to address exercise-related barriers [ 51 , 52 ]. Additionally, extending participant inclusion into a longer recovery time period after cancer treatment would open opportunities for participants dealing with ongoing cancer-related impairments.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, community-based programs offer the opportunity to bring individuals with cancer together to create their own supportive environment and can help build social networks that encourage positive behavior change [ 60 ]. Fifty percent of exercise participants in this trial opted to continue on a fee-for-service basis, with identified facilitators including the support and mentorship of cancer peers, as well as having trained and qualified exercise professionals leading and supporting the classes [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many barriers exist to successful implementation, such as the training/qualifications of interventionists, participant recruitment, and failing to reach those most in need of programming. This project used multiple implementation strategies 19 to address these barriers, including developing structured training for community health educators; adapting the evidence‐based intervention 17 ; locating the program at sites convenient to participants 29 ; and leveraging a community‐academic partnership and building a network of relationships with community organizations to obtain funding and facilitate implementation. Successful implementation of physical activity programs for cancer survivors must consider not only the intervention evidence base but also the strategies used to implement and sustain the intervention.…”
Section: Discussionmentioning
confidence: 99%